The Puklen intrusion, Nunarssuit, SW Greenland A preliminary account of a new Gardar intrusion - Pulvertaft, T. C. R. (Meddelelser om Grønland, 2026)
The Puklen Intrusion is a small elongate complex situated in Nunarssuit, SW. Greenland. It was emplaced in Ketilidian basement, and cut off and hornfelsed Gardar dolerites. The four component members of the intrusion are augite syenite, quartz syenite, soda granite and granophyre, emplaced in that order. It seems that these components represent a differentiation sequence from augite syenite. This is of interest owing to the widespread occurrence of augite syenite (with fayalite) in the Gardar province of SW. Greenland.